MECHANOMEDICINE: applications of mechanobiology to medical sciences and next-generation medical technologies - NARUSE, Keiji (J Smooth Muscle Res, 2018)
Mechanical stress underlies most aspects of cell and organismal biology. Mechanomedicine is a field of biology that seeks to understand molecular, cellular, tissue, organ, and individual responses to mechanical stimuli and aims to apply the gained knowledge to improve health. Combining biology and engineering, we explore research areas including mechanosensitive ion channels, heart failure, and regenerative medicine.This review will describe our findings in mechanobiology, our establishment of a joint venture business as we developed devices responding to medical needs, and our alliance with other companies.